Perlindungan Pengetahuan Tradisional sebagai Hak Konstitusional di Indonesia - Reh Bungana Beru Perangin-angin; Ramsul Nababan; Parlaungan G. Siahaan (Jurnal Konstitusi, 2020)
Indonesia is a country that has abundant genetic resources, multi ethnicity, and diverse cultures. This situation makes Indonesia very rich in traditional knowledge. Protecting traditional knowledge is very important because traditional knowledge is the identity of the community as the owner. Through Article 18B Paragraph (2) and Article 28I Paragraph (3) of the 1945 Constitution, traditional knowledge which is a traditional right and the identity of the indigenous culture are implicitly recognized as constitutional rights. Protection of traditional knowledge in Indonesia is regulated in the Copyright Law, Patent Law, and Culture Promotion Act. However, the protection of traditional knowledge in Indonesia has not been optimal, because it has not provided adequate protection to traditional knowledge.